Inovação na pequena empresa: desvendando conceitos, modelos e políticas de inovação - Lima, Glessia Silva de (2018)
The field of innovation has developed around applied research in large companies and use of R & D as a source of innovation. This development has led to innovation assumptions that are not well suited to the context of small business innovation. Given these considerations, we support the thesis that innovation assumptions need to be revised to accommodate small business. In order to do this, we deal with three main aspects: the field of innovation, the context of generating innovation in small companies and innovation policies. The thesis was developed in the format of three articles. The first article, set forth in Chapter 1, is a theoretical essay and aims to 'discuss how innovation research in small business must be operationalized.' The second article, set out in Chapter 2, is a multiple case study and aims to 'understand how the manager/owner generates innovation in the small business.' The third article, presented in Chapter 3, is a documentary study and aims to analyze the adequacy of innovation policies for the development of the small business and the country. As a contribution, the insights generated in this thesis can guide innovation research in small enterprises, improve the practice of innovation in these organizations and guide the formulation of more appropriate innovation policies.